The role of microbial agents in the pathogenesis of inflammatory bowel disease - Nur Huda Faujan; Mustafa, S; Manaf, MYA; Yee, LY; Abu Bakar, F (Lippincott Williams & Wilkins, 2024)
Indexed by WOS/SCOPUS